Molecular dynamics simulations Of oleyl oleate nano-emulsion systems - Mohammad Lalif, Muhammad Alif (2009)

(untitled)
Problems associated with transdermal drug delivery were directly associated with the skin barrier which is the lipid bilayer at the stratum corneum. Chemical penetration enhancers provide effective solution to these problems. In this research, the potentials of the nano-emulsions of palm-based esters to act as chemical penetration enhancers were studied using computer simulations. The structural and dynamical properties of the nano-emulsions were studied using molecular dynamics simulation (MD) method as the research was focused on the structure of swollen micelles that resulted from solubilization of surfactants in the nano-emulsions system. The micelle system studied consisted of oleyl oleate (OE) with non-ionic surfactants, Span 20 (S20) and Tween 80 (T80) which was simulated in the presence of explicit solvent. Five sets of simulations UPLOAD were performed to determine the most suitable composition for OE/S20 swollen micelles system. The Critical Mixed Micelle Concentration (CMMC) was determined at the region of 10% to 20% of micelle composition by measuring the surface tension of each composition studied. The simulation showed the tendency of OE/S20 mixture to form a cylindrical micelle structure. The stability of OE/S20 swollen micelle system under different temperatures was investigated by running MD simulation on OE/S20 swollen micelle at 300K, 350K and 400K. Temperature at 350K and 400K exhibited expansion of the micelle structure and was explained by the analysis of the radius of gyration (Rg) and radial distribution function g(r) after 2.5 ns of simulation along with the entropy calculations. The effect of different hydrophobicity and hydrophilicity of the non-ionic surfactants used in the formulation of the nano-emulsions was described by the gyration plot and the eccentricity calculation. OE/T80 swollen micelle system exhibited the lowest eccentricity value and smallest in size (± 0.1 nm) compared to OE/S20 swollen micelle with the same number of molecules. The self-assembly profile of OE/T80 swollen micelles system was evaluated until 20 ns MD simulation which showed positive results with spherical micelle as the end product. The aggregate size distribution pattern explained the self-assembly characteristics of the swollen micelles system. However, the reverse-formation that one would expect in such system was not observed throughout 20 ns of MD simulation. Several properties such as hydrophobic mechanism, shapes and sizes of the resulting structure suggested that OE swollen micelles produced can be utilized as chemical penetration enhancers for transdermal drug delivery.